Method of Team Games with Truth Game Media and Challenges to Improve The Ability Study Exposition Text in High School Students - Anindyarini, Atikah; Wijayanti, Kenfitria Diyah; Janah, Ni’matun (Universitas Sebelas Maret, 2019)
Based on this, the study aims to improve the activity and learning outcomes of the ability to study the exposition text in grade XI students of SMA Negeri 3 Surakarta. This research is a class action study with two cycles. Based on data analysis, in the pre cycle, the process of learning monotonous assignments and questioning so that the activation and learning outcomes are still low. In cycle I, activity and learning outcomes experienced a significant increase but had not yet reached an achievement indicator. In cycle II, increased activation and learning outcomes are not very significant compared to the increase in the pre cycle to the I cycle. However, the results have reached an achievement indicator so that learning is said to be successful. It was concluded that the application of the Teams Games Tournament method with the media game Truth and Dare could improve the activity and learning results of the ability to study the exposition text in students XI MIPA 4 SMA Negeri 3 Surakarta.